Knowledge of students of selected universities about expanding professional competence of nurses and midwives with reference to prescribing medicines, writing out prescriptions, and referring for diagnostic tests - Gotlib, Joanna; Belowska, Jarosława; Gorzkiewicz, Anna; Mazur, Nicole; Pietruszewska, Katarzyna; Iwanow, Lucyna; Leszczyński, Piotr; Panczyk, Mariusz; Zarzeka, Aleksander; Samoliński, Łukasz (Polish Journal of Public Health, 2016)
Introduction. Since January 1st, 2016, particular groups of nurses and midwives in Poland are allowed to write prescriptions and refer patients to diagnostic procedures without doctors’ involvement. Aim. The aim of the study was to assess what university students know about the changes that expanded the professional competencies of nurses and midwives. Material and methods. The study group comprised of 535 students of three different universities. The group was 82% female and the mean age was 23 years (min.=19; max.=58, SD=4.780). Nursing students were the largest group among the study participants (177 individuals which meant 33% of the total), followed by Medicine students (145 individuals, 27% of all), Midwifery (107 persons, 20% of the total), and Public Health (100 persons, 19% of all). As many as 324 respondents (60%) had never participated in any medical law-related courses. A voluntary and anonymous survey containing 39 questions divided into 3 parts: 13 questions about knowledge, 26 statements concerning attitudes using a Likert scale, 8 demographic questions) was used. Obtaining an approval from the University’s Ethical Review Board was not required. Pearson’s chi-square test was used to compare frequency of the correct answers by students of every major. The Kruskal-Wallis rank test with a post-hoc analysis for multiple comparison of mean rank sums, STATISTICA version 12.5 (StatSoft, Inc.), licensed to MUW, α=0.05, were used to calculate the differences in summative points for correct answers. Results. Nursing students were significantly more likely to choose the correct answers, unlike Medicine or Public Health students (p